2011
DOI: 10.1002/cncr.26346
|View full text |Cite
|
Sign up to set email alerts
|

Racial variation in breast cancer treatment among Department of Defense beneficiaries

Abstract: BACKGROUND Although the overall age-adjusted incidence rates for female breast cancer are higher among whites than blacks, mortality rates are higher among blacks. Many attribute this discrepancy to disparities in healthcare access and to blacks presenting with later stage disease. Within the Department of Defense (DoD) Military Health System all beneficiaries have equal access to healthcare. The aim of this study was to determine if breast cancer treatment varied between white and black female breast cancer p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 25 publications
0
11
1
Order By: Relevance
“…Sponsor military rank was classified as officer, enlisted junior (lowest four ranks in any branch of service), senior enlisted (noncommissioned officers), and other (warrant officers and cadets). In line with prior research using TRICARE data, sponsor military rank was considered a proxy for socioeconomic status in this analysis with individuals in the enlisted junior category maintained to be representative of those in lower socioeconomic circumstances [6,16,18,22]. The type of surgical intervention was determined using ICD-9 procedure codes and defined as discectomy, decompression, posterolateral fusion, and interbody fusion using a previously published algorithm [17].…”
Section: Methodsmentioning
confidence: 99%
“…Sponsor military rank was classified as officer, enlisted junior (lowest four ranks in any branch of service), senior enlisted (noncommissioned officers), and other (warrant officers and cadets). In line with prior research using TRICARE data, sponsor military rank was considered a proxy for socioeconomic status in this analysis with individuals in the enlisted junior category maintained to be representative of those in lower socioeconomic circumstances [6,16,18,22]. The type of surgical intervention was determined using ICD-9 procedure codes and defined as discectomy, decompression, posterolateral fusion, and interbody fusion using a previously published algorithm [17].…”
Section: Methodsmentioning
confidence: 99%
“…The linked database from the Department of Defense (DoD)’s Central Cancer Registry (CCR) and the MHS Data Repository (MDR) was used in this study and described previously (39, 40). The CCR contains information on cancer patients diagnosed or treated at military treatment facilities (MTFs).…”
Section: Methodsmentioning
confidence: 99%
“…Despite the overall improving survival for women with breast cancer in the United States, survival rates for Black women have not improved at the same rate as white women [13]. Additionally, studies have demonstrated that access to adjuvant therapy alone is insufficient to account for the persistent racial disparities in outcomes [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%